Personal protective equipment for viral hemorrhagic fevers. Issue 4 (August 2019) - Raj, Deepa; Hornsey, Emilio; Perl, Trish M.
Abstract : Purpose of review: Viral hemorrhagic fevers (VHF) encompass many organisms that have caused sporadic outbreaks with high case fatality rates. This article reviews VHF with reported human-to-human transmission and describes updates about personal protective equipment (PPE) for healthcare personnel (HCP) and others. We summarize existing information about appropriate PPE use, training, and compliance for care of VHF patients in endemic and nonendemic countries, as well as addresses the challenges HCP experience when using PPE. Recent findings: PPE is essential in protecting HCP from exposure to disease-causing pathogens. Recent evidence shows that anyone involved in care, management, and transport of certain VHF patients must use elements of PPE as part of appropriate infection prevention and control (IPC) practices. Strict adherence to standard precautions has effectively interrupted human-to-human transmission of a number of VHF. However, unclear protocols, inconsistent training, climate challenges, and cultural sensitivities impede proper PPE use. Appropriate PPE use can drastically reduce the risk of HCP exposure to VHF. Summary: Infections caused by certain VHFs can be highly pathogenic and associated with significant morbidity and mortality. Though it is well documented that use of PPE and good IPC practices are critical to reducing transmission, little conclusive evidence exists about the ideal PPE ensemble or components. Concerns with comfort, compliance, training, and usability may impede proper PPE use. Basic PPE elements, used appropriately as part of stringent IPC, must always form the foundation of care for HCP-treating patients with VHF. More research is required to identify the ideal PPE ensemble for caring for VHF patients in various settings.